Neurologically Healthy Humans’ Ability to Make Saccades Toward Unseen Targets - Olkoniemi Henri; Hurme Mikko; Railo Henry (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Some patients with a visual field loss due to a lesion in the primary visual cortex (V1) can shift their gaze to stimuli presented in their blind visual field. The extent to which a similar "blindsight" capacity is present in neurologically healthy individuals remains unknown. Using retinotopically navigated transcranial magnetic stimulation (TMS) of V1 (Experiment 1) and metacontrast masking (Experiment 2) to suppress conscious vision, we examined neurologically healthy humans' ability to make saccadic eye movements toward visual targets that they reported not seeing. In the TMS experiment, the participants were more likely to initiate a saccade when a stimulus was presented, and they reported not seeing it, than in trials which no stimulus was presented. However, this happened only in a very small proportion (-8%) of unseen trials, suggesting that saccadic reactions were largely based on conscious perception. In both experiments, saccade landing location was influenced by uncon-scious information: When the participants denied seeing the target but made a saccade, the saccade was made toward the correct location (TMS: 68%, metacontrast: 63%) more often than predicted by chance. Signal detection theoretic measures suggested that in the TMS experiment, saccades toward unseen targets may have been based on weak conscious experiences. In both experiments, reduced visibility of the target stimulus was associated with slower and less precise gaze shifts. These results suggest that saccades made by neurologically healthy humans may be influenced by unconscious information, although the initiation of saccades is largely based on conscious vision.(c) 2023 The Author(s). Published by Elsevier Ltd on behalf of IBRO. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).